Laughter and crying as bodily expressions of crisis situations and their literary shaping. Anton Čechov's Dramas in the Light of Helmuth Plessner's Philosophical Anthropology - Mirkovic, Nikola (Scenari, 2021)
The relation between art and the human body is not only an important issue for contemporary art practices but has been explored by philosophical anthropologists as well. Helmuth Plessner took particular interest in the corporeality and aesthetic experience of acting. In his treatise On the Anthropology of the Actor (1948), Plessner described acting as a form of art in which the human being represents the medium and the message at the same time. Actors use their bodies to convey an image of a character. Plessner compares this process to the way we perform social roles in everyday life. Yet, in the situation of a personal crisis images can fall apart. In his plays, Anton Chekhov reflects on the meaning of broken images masterfully. In this essay, we consider crucial moments from Chekhov’s plays in order to understand how people cope with profound disappointments and the loss of meaning. Furthermore, a postmodern staging of Chekhov’s The Seagull (1896) – which exemplifies the physical dimension of a personal crisis – is taken into account. Finally, the tragicomic aspects of Chekhov’s plays are interpreted with the help of Plessner’s Laughing and Crying (1941). Plessner’s theory of expressive behavior emphasizes the role of the human body for understanding human nature and art.